Quantitative Imaging With DNA-PAINT for Applications in Synaptic Neuroscience - Unterauer, Eduard M.; Jungmann, Ralf (Frontiers in Synaptic Neuroscience, 2022)
Super-resolution (SR) microscopy techniques have been advancing the understanding of neuronal protein networks and interactions. Unraveling the arrangement of proteins with molecular resolution provided novel insights into neuron cytoskeleton structure and actin polymerization dynamics in synaptic spines. Recent improvements in quantitative SR imaging have been applied to synaptic protein clusters and with improved multiplexing technology, the interplay of multiple protein partners in synaptic active zones has been elucidated. While all SR techniques come with benefits and drawbacks, true molecular quantification is a major challenge with the most complex requirements for labeling reagents and careful experimental design. In this perspective, we provide an overview of quantitative SR multiplexing and discuss in greater detail the quantification and multiplexing capabilities of the SR technique DNA-PAINT. Using predictable binding kinetics of short oligonucleotides, DNA-PAINT provides two unique approaches to address multiplexed molecular quantification: qPAINT and Exchange-PAINT. With precise and accurate quantification and spectrally unlimited multiplexing, DNA-PAINT offers an attractive route to unravel complex protein interaction networks in neurons. Finally, while the SR community has been pushing technological advances from an imaging technique perspective, the development of universally available, small, efficient, and quantitative labels remains a major challenge in the field.